Does distributed leadership fit the paradigm transformation of secondary school effectiveness in Nigeria? - Bashir, Karima; Alam, Gazi Mahabubul (Inderscience Publishers, 2024)
Distributed Leadership (DL) has gradually been identified as a leadership model that needs to be customised to suit the desired expectations based on a differentiated school context. This article aims to explore the notion – why one size does not fit all, in recognition with the DL and school effectiveness in a decentralised context. The paper employs the qualitative method using semi-structured interviews and document reviews to make its argument. The selected sampled principals from the federal secondary schools located in north-western Nigeria provided valuable insights. The findings indicate that secondary school principals tend to implement a leadership model that emphasises sharing responsibilities and participation in decision-making, aligning with the country’s transformation of the leadership paradigm. These findings suggest that decentralised systems and DL alone are not the exclusive remedy for fixing ineffective schools. In conclusion, this paper enriches the existing literature on contextualisation of DL by proposing a comprehensive and integrated leadership model suitable for decentralised schools.